Non-financial liabilities and effective corporate restructuring - Bo Becker; Jens Josephson (Research Institute of Industrial Economics (IFN), 2024)
Many countries' insolvency systems focus on restructuring financial liabilities, and ignore operational liabilities such as leases and long-term supplier contracts. We model insolvency procedures with and without operational restructuring options. Such options avoid excessive liquidation of firms with significant non-financial obligations. Ex-ante, this option should increase debt capacity, especially in industries with inputs supplied under executory contract. We test this hypothesis around the introduction of a new law in Israel which facilitated the rejection of contracts, and by comparing capital structures for industries with high lease obligations between the U.S. and other countries. Empirical results confirm that operating restructuring is a key aspect of insolvency.
Keywords: G32; G33; 330; Bankruptcy; Restructuring; Executory contracts